2023
DOI: 10.1111/cpr.13551
|View full text |Cite
|
Sign up to set email alerts
|

Omega‐3 polyunsaturated fatty acids and its metabolite 12‐HEPE rescue busulfan disrupted spermatogenesis via target to GPR120

Jun Jing,
Lei Ouyang,
Hong Zhang
et al.

Abstract: Busulfan is an antineoplastic, which is always accompanied with the abnormal of spermatogonia self‐renewal and differentiation. It has been demonstrated that the omega‐3 polyunsaturated fatty acids (PUFAs) benefits mature spermatozoa. However, whether omega‐3 can protect endogenous spermatogonia and the detailed mechanisms are still unclear. Evaluate of spermatogenesis function (in vivo) were examined by histopathological analysis, immunofluorescence staining, and western blotting. The levels of lipid metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
(138 reference statements)
0
1
0
Order By: Relevance
“…However, low level of T and high level of ROS are commonly observed. It has been reported that BUS administration could significantly increase ROS in spermatogonia and inhibit its differentiation and proliferation ( Jing et al, 2023 ). ROS is a double-edged sword in spermatogenesis, high level of ROS could lead to oxidative stress and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…However, low level of T and high level of ROS are commonly observed. It has been reported that BUS administration could significantly increase ROS in spermatogonia and inhibit its differentiation and proliferation ( Jing et al, 2023 ). ROS is a double-edged sword in spermatogenesis, high level of ROS could lead to oxidative stress and cell death.…”
Section: Discussionmentioning
confidence: 99%